Proceedings 3rd Mytribos Symposium 2019 Universiti Malaysia Perlis (UniMAP) - Sulaiman, Mohd Hafis (Tribology & Metal Forming Research Group, 2019)
The aim of the symposium is to promote proper practices in research and development, and to provide a forum for practicing engineers and scientists from different disciplines to exchange ideas and experience related to the field of tribology in Malaysia. Subjects like lubrication, friction, wear, surface engineering, surface treatments and coating are scopes of interest. The symposium value collaborations between academia and industry in all possible endeavors.